Factors influencing audiologists' perception of moral climate in the workplace. (4th May 2018) - Simpson, Andrea; Phillips, Kendall; Wong, Danny; Clarke, Sandy; Thornton, Michelle
Abstract: Objective : The purpose of this study was to assess audiologists' perceptions of ethics and moral climate in the workplace. Design : The Ethics Environmental Questionnaire (EEQ) was sent out to all audiologists registered with the professional body Audiology Australia. Participants were also invited to undertake a semi-structured interview. Study sample : A total of 301 audiologists completed the questionnaire. Eight of these participants also agreed to complete the interview. Results : The overall mean on the EEQ was approximately equivalent to that of a positive ethical environment, with the exception of those working in adult rehabilitation settings who scored significantly poorer. Scores were significantly associated with state and age. Qualitative analysis from the interviews found that sales pressure from employers was the dominant cause for concern amongst the group. Conclusions : For those working in adult rehabilitation, moral distress is most likely to occur as the result of conflicting goals between the organisation and the audiologist. There is a need to regulate the practice at an organisational as well as individual level to ensure the focus remains on ethical practice.